AB0781 High Sensitivity of the ASAS Classification Criteria in Patients with HLA-B27 Positive Undifferentiated Spondyloarthritis with Onset of Disease After Age 45. (9th June 2015) - Gilio, M.; Olivieri, I.; D'Angelo, S.; Padula, A.; Leccese, P.; Di Bello, S.; Palazzi, C.; Ferrara, N.; Akkoc, N.
Abstract : Background: The spondyloarthritis (SpA) complex also includes forms that do not meet criteria for the definite forms and are called undifferentiated SpA (uSpA). Recently the Assessment in SpondyloArthtritis international Society (ASAS) suggested criteria for axial and peripheral SpA that have substituted the Amor and the European Sondylarthropathy Study Group (ESSG) criteria for all forms of SpA. In the ASAS criteria for axial disease the entry criterion is chronic low back pain in a patient with an age less than 45 years. Only 15% of the patients included in the study for the ASAS criteria for peripheral disease were older than 45 years. Objectives: The objective of our study was to evaluate the sensitivity of the ASAS criteria for axial and peripheral SpA in a cohort of consecutive patients with HLA-B27 positive uSpA with onset of disease after the age of 45 (late onset uSpA) consecutively recruited in a 12-year period in comparison with a cohort of consecutive patients with HLA-B27 positive uSpA with onset before age 45 (ordinary onset uSpA) recruited in the same period. Methods: Patients HLA-B27 positive with at least one clinical manifestation of SpA and not meeting the New York criteria for ankylosing spondylitis (AS) and with a negative personal history for psoriasis, inflammatory bowel disease and preceding infection seen since January 2001 were entered in a special register and were followed prospectively. Each patient was examined at 6-month interval even if asymptomatic. Results: During the 12-year recruitment period, 93 patients (35 M, 58 F; age 58.4±9.8) with late onset uSpA were seen. The first 93 consecutive patients (54 M, 39 F; age 29.6±8.6) with ordinary onset uSpA seen in the same period were evaluated for comparison. Compared to the 93 patients with ordinary onset uSpA, the 93 patients with late onset uSpA were more frequently females (62.4% vs. 41.9%, p<0.05) had a significant shorter diagnostic delay (time elapsed between the day of onset and the day of diagnosis) (24.2±45.6 vs. 65.1±97 months, p<0.05) and showed more frequently increased levels of ESR (Erythrocite Sedimentation Rate)(57% vs. 33.3%, p<0.05) and CRP (C-reactive proteine) (62, 4% vs. 48, 4%, p=0, 07). In addition, patients with late onset uSpA developed more frequently inflammatory extremity swelling with pitting edema (IESPE) over the dorsum of hands and/or of the feet (25.8% vs. 4.3%, p<0.01) and peripheral enthesitis (48.4% vs. 31.2%, p<0.05). In contrast, patients with ordinary onset uSpA showed more frequently acute anterior uveitis (20.4% vs. 7.5%, p<0.05). The sensitivity of the ASAS criteria was similar in the ordinary onset (90.3%) and the late onset (91.4%) cohorts of patients with uSpA. Conclusions: The ASAS classification criteria for axial and peripheral SpA showed a similar high sensitivity in patients with ordinary and late onset uSpA. In addition, this study confirms that some clinical and laboratory features of SpA may differ with the age at onset of the disease. Disclosure of Interest: None declared